The Effect Of Sexual Relationship Health Education During Pregnancy On The Anxiety Of Primigravid Mothers In The New Normal Period - Ayu Galuh Wibowo; Tina Mawardika (Jurnal Smart Keperawatan, 2023)
Sexual intercourse during pregnancy is still a taboo among the people around Ungaran City, Semarang Regency, giving rise to anxiety and concern about fulfilling sexual needs during pregnancy which generally occurs among primigravida mothers due to a lack of experience and knowledge regarding sexuality during pregnancy. The aim of the study was to determine the effect of health education on sexual intercourse during pregnancy on anxiety among primigravida mothers. Quantitative method by way of quasi experiment, nonequivalent control group design approach. The first group was given health education through animated video media and the other group was not given any treatment. Measuring tool with a questionnaire that is measured comparatively analytically in pairs. The research sampling technique used purposive sampling. The population in this study were 376 pregnant women and the research sample was 38 primigravida mothers who live in Ungaran City, Semarang Regency. Analysis used the Mann Whitney test with a value of α (0.05). Results: Statistical test results using the Mann Whitney test obtained Z count (-2.634) > Z table -1.96 and p-value (0.008) < α (0.05). Conclusion: There is an effect of health education about sexual intercourse during pregnancy on the anxiety level of primigravida mothers. Keywords: sexual relationship; worry; primigravidaPengaruh Pendidikan Kesehatan Hubungan Seksual Selama Kehamilan Terhadap Kecemasan Ibu Primigravida Pada Masa Kenormalan BaruABSTRAK Hubungan seksual selama masa kehamilan masih menjadi hal yang tabu di kalangan masyarakat sekitar Kota Ungaran, Kabupaten Semarang, sehingga menimbulkan kecemasan dan kekhawatiran mengenai pemenuhan kebutuhan seksual pada masa kehamilan yang umumnya sering terjadi pada ibu primigravida karena kurangnya pengalaman dan pengetahuan terkait seksualitas selama kehamilan. Tujuan penelitian untuk mengetahui pengaruh pendidikan kesehatan tentang hubungan seksual selama masa kehamilan terhadap kecemasan pada ibu primigravida. Metode secara kuantitatif dengan cara quasi experiment, pendekatan nonequivalen control grup design. Kelompok pertama diberi pendidikan kesehatan melalui media video animasi dan kelompok lain tidak diberi perlakuan. Alat ukur dengan kuesioner yang diukur secara analitik komparatif berpasangan. Teknik pengambilan sampling penelitian menggunakan purposive sampling. Populasi dalam penelitian ini sebanyak 376 ibu hamil dan sampel penelitian berjumlah 38 ibu primigravida yang berdomisili di Kota Ungaran Kabupaten Semarang. Analisis menggunakan uji Mann Whitney dengan nilai α (0,05). Hasil: Hasil uji statistik dengan menggunakan uji mann whitney diperoleh nilai Z hitung (-2,634) > Z tabel -1,96 dan nilai p-value (0,008) < α (0,05). Simpulan: Ada pengaruh pendidikan kesehatan tentang hubungan seksual selama masa kehamilan terhadap tingkat kecemasan ibu primigravida. Kata kunci: hubungan seksual; kecemasan; primigravida